Al-Ṣuwaydirah (old al-Ṭaraf) and its Early Islamic inscriptions - al-Rashid, Saad Bin ʿAbdulaziz (Proceedings of the Seminar for Arabian Studies, 2011)
The present town and the old site of al-Ṣuwaydirah are located c.62 km to the east of al-Madīnah al-Munawwarah in a lowland area surrounded by hills, and can only be seen from a short distance away. It is an ancient settlement, a camping station for pilgrims and caravans and an important source of water, which attracted people to stay there not only in the early Islamic period but also long before, in prehistoric times. Muslim geographers, historians, and writers provided brief but very important information on al-Ṣuwaydirah. The name itself became known in the fifteenth century AD when the Mamlūk Sultan Qāʾit Bay carried out a major renovation and restoration of the Prophet’s Mosque (al-Masjid al-Nabawī al-Sharīf) after it was damaged by fire. The name ’Ṣuwaydirah’ originally referred both to an ancient well (biʾr), which is still in use, and to Wādī al-Ṣuwaydirah. In fact the area of al-Ṣuwaydirah was known in the Early Islamic period as al-Ṭaraf. Muslim geographers referred to al-Ṭaraf as a pilgrim station on the intersection of roads from the route called Darb Zubaydah to al-Madīnah. This paper sheds light on valuable information on the archaeology, history, and rock art of al-Ṣuwaydirah.